Development of a low-cost water treatment technology using Moringa oleifera seeds - Barajas, John Raymond B. (Animo Repository, 2015)
The persistent poor access to safe drinking water in low-income regions necessitates the development of low-cost alternatives to available yet expensive water treatment technologies. To address this need, this research investigates the development of a biofilter using the seeds of Moringa oleifera (MO), an indigenous tree in many low-income countries. The protein extracts from the MO seeds have been previously used as a disinfectant and coagulant in water treatment. However, the extraction of the protein leaves behind undesired organics that cause problems in water storage. To eliminate these organics, we immobilized the MO protein extracts onto three adsorbents (sand, commercial activated carbon, and burnt rice husk), and then tested the use of the MO-functionalized adsorbents in E. coli disinfection. The sorption and disinfection studies were carried out using batch equilibrium tests. We implemented a multi-level factorial design to investigate the factors affecting the adsorption and disinfection processes. Results show that the MO protein binds strongly to all adsorbents, and that bound proteins are not released back into the solution. The MO adsorption capacity was highest in activated carbon and lowest in sand. The functionalized adsorbents were able to deactivate E. coli with the highest coliform removal observed in rice husk and activated carbon. Results of one-way ANOVA indicate that the type of adsorbent material is an important factor in E. coli disinfection using MO functionalized adsorbents. However, there is no sufficient evidence to conclude that activated carbon is superior to rice husk. Overall, these results suggest the possibility of designing a low-cost biofilter that uses MO immobilized adsorbents as packing material. © 2015 IEEE.